APPLICATION OF FRENCH AGRICULTURAL EXPERIENCE IN UKRAINE IN THE SECOND HALF OF THE 19TH CENTURY - Batіuk , Alla (Collection of scientific papers «ΛΌГOΣ», 2022)
Over the centuries, humanity has overcome the difficult path to a stable food situation in the world. However, Russia's full-scale war against Ukraine, which began on February 24, 2022, put the world in front of another food crisis. Ukraine is an important exporter of everyday consumer products: sunflower oil, fats and cereals, will not be able to fully produce and export them. However, the crisis threatens not only those countries that depend on Ukrainian exports, but also those whose economies are suffering as a result of military aggression. In this article we will consider the influence of the achievements of French agronomists of the second half of the 19th century on the formation of a powerful agricultural industry in Ukraine.